Design of miniaturized branch‐line coupler based on novel spiral‐interdigital resonator cells. Issue 11 (26th August 2013) - Guo‐Cheng, Wu; Guang‐Ming, Wang; Bo, Sun; Ya‐Wei, Wang
ABSTRACT A miniaturized branch‐line coupler operated at 2.15 GHz, which is based on the novel spiral‐interdigital resonator cells, is proposed in this letter. The electromagnetic characteristics of the novel spiral‐interdigital resonator cell are analyzed by simulator and equivalent circuit model, and the results prove that it has a frequency with phase of −90° in the passband. Then, the proposed branch‐line coupler is designed, fabricated, and measured; the measured and simulated results are in good agreement, showing that this proposed branch‐line coupler has good electromagnetic performances. Moreover, the whole size of the proposed branch‐line coupler is 11.55 × 18.6 mm2, which is only 27.6% of the conventional one, and the miniaturization has realized effectively. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2750–2753, 2013